2018
DOI: 10.1002/jcsm.12335
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ischaemic stroke induces transient cardiac atrophy and dysfunction

Abstract: Background Stroke can lead to cardiac dysfunction in patients, but the mechanisms underlying the interaction between the injured brain and the heart are poorly understood. The objective of the study is to investigate the effects of experimental murine stroke on cardiac function and molecular signalling in the heart. Methods and results Mice were subjected to filament‐induced left middle cerebral artery occlusion for 30 or 60 min or sham surgery and underwent repetitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 41 publications
(76 reference statements)
2
35
0
Order By: Relevance
“…MicroRNA also plays an important role in brain–heart interaction (Han et al 2015 ; Min 2009 ). Chen et al ( 2017b ) found in the study that compared with non-stroke animals, stroke mice have significantly lower heart EF, meanwhile, atrogin-1 and E3 ubiquitin ligase murf-1 were elevated, and the transcription factor peroxisome proliferative activated receptor was a potential mediator of transcriptional dysregulation in stroke-related myocardial atrophy (Veltkamp 2019 ). At the same time, stroke significantly increased macrophage infiltration and increased levels of Interleukin-1(IL-1), Interleukin-6(IL-6), Monocyte-chemoattractant protein-1(MCP-1), tumor necrosis factor-β(TGF-β) and macrophage-related inflammatory cytokines in the heart, and induced cardiac fibrosis (Yan 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA also plays an important role in brain–heart interaction (Han et al 2015 ; Min 2009 ). Chen et al ( 2017b ) found in the study that compared with non-stroke animals, stroke mice have significantly lower heart EF, meanwhile, atrogin-1 and E3 ubiquitin ligase murf-1 were elevated, and the transcription factor peroxisome proliferative activated receptor was a potential mediator of transcriptional dysregulation in stroke-related myocardial atrophy (Veltkamp 2019 ). At the same time, stroke significantly increased macrophage infiltration and increased levels of Interleukin-1(IL-1), Interleukin-6(IL-6), Monocyte-chemoattractant protein-1(MCP-1), tumor necrosis factor-β(TGF-β) and macrophage-related inflammatory cytokines in the heart, and induced cardiac fibrosis (Yan 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight loss after neurological stroke is frequently observed in clinical and experimental settings and associated with adverse clinical outcome . The consequences of ischaemic stroke on myocardium have been investigated in an experimental study by Veltkamp et al ., which showed a transient myocardial dysfunction and atrophy of cardiomyocytes following the brain ischaemia. Further clinical studies investigating cachexia and muscle wasting in patients with stroke are warranted.…”
mentioning
confidence: 99%
“…Together with the finding that half of the patients with AIS with markedly elevated cTn had no coronary artery disease at all, this implies that alternative mechanisms beyond ACS may play an important role [17]. This is supported by animal research and clinical and neuroimaging studies, suggesting that stroke-associated myocardial injury may originate from structural and/or functional interference within the central autonomic nervous system (CAN) with an overshooting sympathetic response [18][19][20]. On a cellular basis, it is assumed that excessive catecholamine and cortisol levels lead to an increased sarcoplasmic calcium influx with a consecutive hypercontraction of the sarcomeres, electrical instability, and metabolic and oxidative stress.…”
Section: Introductionmentioning
confidence: 90%